2020
DOI: 10.15252/emmm.202012642
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for targeting complement in COVID‐19

Abstract: A novel coronavirus, SARS‐CoV‐2, has recently emerged in China and spread internationally, posing a health emergency to the global community. COVID‐19 caused by SARS‐CoV‐2 is associated with an acute respiratory illness that varies from mild to the life‐threatening acute respiratory distress syndrome (ARDS). The complement system is part of the innate immune arsenal against pathogens, in which many viruses can evade or employ to mediate cell entry. The immunopathology and acute lung injury orchestrated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 132 publications
(160 reference statements)
2
124
0
2
Order By: Relevance
“…With the extensive complement activation and widespread endothelial destruction, inhibition of complement pathways may also represent a favorable therapeutic target [ 61 , 62 ]. Compassionate use of the C3 inhibitor AMY-101, as well as the anti-CD5 monoclonal antibody eculizumab have shown anecdotal success [ [63] , [64] , [65] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the extensive complement activation and widespread endothelial destruction, inhibition of complement pathways may also represent a favorable therapeutic target [ 61 , 62 ]. Compassionate use of the C3 inhibitor AMY-101, as well as the anti-CD5 monoclonal antibody eculizumab have shown anecdotal success [ [63] , [64] , [65] ].…”
Section: Discussionmentioning
confidence: 99%
“…Compassionate use of the C3 inhibitor AMY-101, as well as the anti-CD5 monoclonal antibody eculizumab have shown anecdotal success [ [63] , [64] , [65] ]. Mannan binding lectin has also been proposed as a therapeutic target given its gatekeeping role in complement activity and endothelial damage [ 66 ]. A number of trials are now underway with inhibitors to complement and mannan binding lectin as novel therapeutic targets [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…That supposition was first supported by promising data from patients treated with complement inhibitors (116)(117)(118)(119). Polycarpou et al (120) suggested that targeting complement might contribute to reducing COVID-19 systemic complications (multiorgan failure, coagulopathy), mediated by lectin pathway activation. Therefore, inhibition of the complement system at the levels of C3 or C5a/ C5aR is considered a possible therapeutic option (121,122).…”
Section: Possible Associations Of Complement Activation Via the Lectimentioning
confidence: 99%
“…A therapeutic anti‐inflammatory strategy against complement has the potential to stem the downstream inflammatory response and capillary leak, and, consequently, lung damage and CARDS, assuming adequate tissue penetration of drug to the site of complement activation [ 95 ]. A number of clinically ready potential therapeutic agents are available.…”
Section: Other Potential Therapiesmentioning
confidence: 99%